Pengembangan Modul Bahasa Inggris Imajinatif Berbasis Aplikasi Chat dalam Komunikasi Klinis Mahasiswa Keperawatan - Trimey Liria Hutauruk; Nurlela M. Nababan; Rita Magdalena Panggabean; Serawati Hutagalung (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
Clinical communication skills in English are an essential competence for nursing students; however, conventional instruction often lacks contextual relevance and provides limited opportunities for active student engagement. This study aimed to develop and evaluate the effectiveness of an imaginative English module, based on a chat application, in enhancing nursing students’ clinical communication skills. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants were 60 nursing students. Data were collected through pre-test and post-test assessments of clinical communication skills. Data analysis included descriptive statistics, paired samples t-test, n-Gain calculation, and effect size analysis using Cohen’s d. The results demonstrated a significant improvement in students’ communication skills following the implementation of the module. The mean score increased from 41.33 in the pre-test to 81.50 in the post-test. The paired samples t-test indicated a statistically significant difference (p < 0.05). The n-Gain value of 67.88% fell within the effective category, while a Cohen’s d value of 4.06 indicated a very large effect size. Correlation analysis revealed that the improvement in communication skills was not strongly dependent on students’ initial performance levels. These findings confirm that the imaginative English module based on a chat application is effective in improving nursing students’ clinical communication skills. The integration of imaginative learning and chat-based technology promotes contextual, interactive, and adaptive learning experiences. This study offers an innovative contribution to the development of technology-enhanced English language instruction in nursing education.